A Review of Ice Particle Shapes in Cirrus formed In Situ and in Anvils. Issue 17 (11th September 2019) - Lawson, R. P.; Woods, S.; Jensen, E.; Erfani, E.; Gurganus, C.; Gallagher, M.; Connolly, P.; Whiteway, J.; Baran, A. J.; May, P.; Heymsfield, A.; Schmitt, C. G.; et al.
Abstract: Results from 22 airborne field campaigns, including more than 10 million high‐resolution particle images collected in cirrus formed in situ and in convective anvils, are interpreted in terms of particle shapes and their potential impact on radiative transfer. Emphasis is placed on characterizing ice particle shapes in tropical maritime and midlatitude continental anvil cirrus, as well as in cirrus formed in situ in the upper troposphere, and subvisible cirrus in the upper tropical troposphere layer. There is a distinctive difference in cirrus ice particle shapes formed in situ compared to those in anvils that are generated in close proximity to convection. More than half the mass in cirrus formed in situ are rosette shapes (polycrystals and bullet rosettes). Cirrus formed from fresh convective anvils is mostly devoid of rosette‐shaped particles. However, small frozen drops may experience regrowth downwind of an aged anvil in a regime with RH ice > 120% and then grow into rosette shapes. Identifiable particle shapes in tropical maritime anvils that have not been impacted by continental influences typically contain mostly single plate‐like and columnar crystals and aggregates. Midlatitude continental anvils contain single‐rimed particles, more and larger aggregates with riming, and chains of small ice particles when in a highly electrified environment. The particles in subvisible cirrus are < 100 μm and quasi‐spherical with some plates and rare trigonal shapes. Percentages of particle shapes and power laws relating mean particle area and mass to dimension are provided to improve parameterization of remote retrievals and numerical simulations. Key Points: There is a distinct difference in the shapes of cirrus ice particles formed in situ and cirrus generated as the result of convective anvils The shapes of ice particles in tropical maritime anvil cirrus are characteristically different from ice particles in midlatitude convective anvils Numerical simulations of the generation of in situ and anvil cirrus can incorporate ice particle shape information to improve radiative transfer parameterizations